SYSTEMATICS OF VAGRANTINI BUTTERFLIES (LEPIDOPTERA: NYMPHAlIDAE). PART 1. CLADISTIC ANALYSIS - Djunijanti Peggie (Treubia, 2003)
Eiglit genera of lndo-Australian butterjiies: Algia. Algiachroa, Cirrochroa, Cupha, Phalanta, Terinos, Vagrans, and Vindula are presented here. These genera together with two Afrotropical genera: Lachnoptera and Smerina, and a Central American genlls Euptoieta were previollsly placed as subiribe uncertain.One-hundred adult morphological characters were scored for fifty-four taxa, and were analyzed simultaneousuj (Nixon and Carpenter, 1993). The cladistic analysis showed that all species were properly assigned to monophyletic genera, and the arrangement of the outgroup taxa is in concordance with the classification previously suggested. The eight lndo-Australian and two Afrotropical genera belong to the tribeVagrantini within the subfamily Heliconiinae.